Symposium on 'The challenge of translating nutrition research into public health nutrition'. Session 3: Joint Nutrition Society and Irish Nutrition and Dietetic Institute Symposium on 'Nutrition and autoimmune disease'. Recent advances in genetic understanding of coeliac disease. - Mc Manus, Ross; Feighery, Conleth (My University, 2009)
Over the past 20 years major advances have been made in the diagnosis and understanding of pathogenic mechanisms relating to coeliac disease. Recently-identified genetic markers support the immunological?inflammatory nature of the disease. It is hoped that these newly-identified genes will assist further dissection of the inflammatory pathways in coeliac disease and give insight into why certain individuals develop intolerance to dietary gluten.
PUBLISHED
Keywords: Nutrition; autoimmune disease; Genes & Society; Immunology, Inflammation & Infection